Golden jackal expansion in northernmost Europe: records in Finland - Kojola, Ilpo; Henttonen, Heikki; Heikkinen, Samuli; Ranc, Nathan (Springer Science and Business Media LLC, 2024)
The Eurasian golden jackal (Canis aureus) has been rapidly expanding its distribution range in Europe. Whether jackals will be able to adapt to new environmental conditions in northern Europe remains largely unresolved. Herein we provide additional evidence for the species’ ability to colonize northern environments by presenting the new records of golden jackal occurrence in Finland. During 2018–2022, golden jackals were recorded at six localities of which one located in southern, four in central and one in northern Finland. We drafted potential main routes of dispersal movements by jackals in northern Europe, and discuss ecology and management of this newly colonizing species in Finland.
Keywords: Mesocarnivore; Range expansion; Long-distance dispersal